A Scoping Review of Nonpharmacological Interventions to Reduce Disability in Older Adults. (19th April 2019) - Wu, Chao-Yi; Rodakowski, Juleen L; Terhorst, Lauren; Karp, Jordan F; Fields, Beth; Skidmore, Elizabeth R
Abstract: Background and Objectives: Minimizing disability is critical to reduce the costly health care associated with disability and maintain quality of life into old age. We examined the effect sizes of nonpharmacological intervention studies in reducing disability and explored the active ingredients of interventions. Research Design and Methods: A scoping review was conducted via PubMed, PsycINFO, and CINAHL databases. Thirty-one randomized controlled trials were included. Eight active ingredients were identified by three experts (exercise, problem-solving, cognitive behavioral therapy, environmental modification, education, goal setting, comprehensive geriatric assessment, and cognitive training). Results: The range of Cohen's d was –0.85 to 1.76 across 31 studies (included 33 interventions); 67% studies ( n = 22) obtained small-to-negative effect sizes ( d = –0.85 to 0.18), accounting for 83% participants across studies. Interventions that incorporated exercise, problem-solving, cognitive behavior therapy, and environmental modification were associated with stronger effect sizes. Interventions that incorporated comprehensive geriatric assessment obtained small effect sizes. Discussion and Implications: Majority of intervention studies found little or no effect in reducing disability for older adults. To optimize the effects of nonpharmacological interventions, we recommend researchers to (i) develop a screening tool for "risk of disability" to inform those who are early on the disability progression, yet not experience any difficulties in activities of daily living and instrumental activities of daily living; (ii) specify the active ingredients embedded in complex interventions to facilitate change in disability; and (iii) select sensitive tools to capture the progression of disability in late life.